Evaluating the impact of different biochar types on wheat germination - Ghenwa Kataya; Zahraa El Charif; Adnan Badran; David Cornu; Mikhael Bechelany; Akram Hijazi; Beshr Sukkariyah; May Issa (Scientific Reports)
Abstract This study assessed sustainable solutions for organic waste management, focusing on biochar derived from kitchen waste. The characteristics and phytotoxicity effects of biochar produced from four different types of kitchen waste were investigated in view of potential agricultural applications. Analysis of the chemical and physical properties of the different biochar samples by X-ray fluorescence and Fourier transform infrared spectroscopy revealed a nutrient-rich composition with carbon, calcium, and potassium contents that ranged from 35 to 48%, from 1.6 to 24%, and from 1.5 to 28.5%, respectively. In phytotoxicity tests, the highest germination rate (45%) was observed with Coffee residue biochar obtained at 300 °C (application rate of 1%) and the longest shoot length (25 cm) with orange peel biochar obtained at 300 °C (application rate of 1%). Germination rate and shoot length were not significantly different between biochar-exposed soils and control soils (without biochar), indicating no toxic effect due to biochar addition. Washing biochar improved germination rates significantly (control: 98%; potato peel biochar: 92%; banana peel biochar: 83%). The longest shoot length (8.3 cm) was obtained with the washed potato peel biochar (pyrolysis temperature = 400 °C) extract. These findings suggest that biochar can be safely used as a soil amendment without harming the environment or hindering plant growth. The Tukey honestly significant difference (HSD) test results further emphasized the influence of different factors, such as pyrolysis temperature and feedstock type, in biochar applications.